Noon- A Journal of Contemporary Art and Visual Culture : 2- Monumental and Unmonumental 2010 - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2010)
Essays: Ai Weiwei, Yongwoo Lee, Kim Uchang, Seung H-sang, Kim Hyun-do, Chalie Gere, Goran Therborn, Jung Ho-gi, Kang Sumi.
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions